If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -2 = -3a + 23 Reorder the terms: -2 + 2a = -3a + 23 Reorder the terms: -2 + 2a = 23 + -3a Solving -2 + 2a = 23 + -3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3a' to each side of the equation. -2 + 2a + 3a = 23 + -3a + 3a Combine like terms: 2a + 3a = 5a -2 + 5a = 23 + -3a + 3a Combine like terms: -3a + 3a = 0 -2 + 5a = 23 + 0 -2 + 5a = 23 Add '2' to each side of the equation. -2 + 2 + 5a = 23 + 2 Combine like terms: -2 + 2 = 0 0 + 5a = 23 + 2 5a = 23 + 2 Combine like terms: 23 + 2 = 25 5a = 25 Divide each side by '5'. a = 5 Simplifying a = 5
| 3w-6x-y+5w+17x-6y= | | v^3-p^3=0 | | h=128t+16t^2 | | 9x^2-25x-94=0 | | x^3+3x^2+7x+21=0 | | 4(t+7)=40 | | 2+17=2m | | h=128+16t^2 | | -2y(1+9x)= | | 4x-3y+10w+4y-2w+7x= | | 2s+5+3+5s= | | A+128-34=286 | | -2(2x-5)-(x-5)=-1 | | 4(x^2+y(y+4))=12x+11 | | -[6z-(11z+9)]=9+(4z+10) | | 3-10u=-57 | | -2(t-4)=10-2r | | 7+7x=4x+3 | | 4=4-2x-4 | | 2x-15=3(5-x) | | (5x-1)(9x+3)=0 | | 6x+11=-7 | | 35mi=cm | | 4w+7y+7x+4x-14y+4w= | | 36y^2+12y+1-x^2= | | 3x+-11=10 | | 2x+119=95 | | 13f+41=-20+5f | | 2f+5f=27 | | 4w+8x+12y+4w+3x-5y= | | 7x-6+x=8x | | 11n=7n+12 |